Role of free hydrochloric acid in the low-cost regeneration of ferric chloride etchant by oxygen gas - Jefferies, P. J. (Cranfield University, 2005)
This thesis concerns the development of a low cost and environment- friendly method for the regeneration of the most widely used aqueous etchant, ferric chloride, found in photochemical machining (PCM) facilities. In order to implement the above process a comprehensive and automated chemical analysis and control system was designed to fully investigate the key parameters which previous research has suggested play a major role in the analysis of ferric chloride. Monitoring methods have been developed and deployed in a commercial environment such that the etchant could be analysed remotely across the business network or via the internet. This level of monitoring has removed much of the `black art' previously associated with etching and has allowed proactive control of the etchant and the PCM process in general. Detailed analysis of the data captured has resulted in a clear understanding of the role the free hydrochloric acid (HC1) level plays in prolonging the life of the etchant. By keeping the free acid level high, dissolved metals remain in solution. The regeneration uses oxygen from the air, combined with surplus HCI, to regenerate the etchant within the etching machine itself. This environment-friendly system has allowed etching to continue in a very controlled way for nearly one year, during which time some 500kg of metal have been dissolved. This has totally eliminated the need to change the etchant which otherwise would have been carried out every 16 weeks. The saving to the sponsoring company has been over £7000 per year. These combined activities are considered as a major advancement in knowledge and will be of considerable benefit to the PCM industry in general. The monitoring systems alone would significantly benefit any PCM company by reducing rejects and improving product quality and productivity.